Mauritania and the Western Sahara: Between Algeria and Morocco (1969-‍1979) - Cordero Olivero, Inmaculada; Lemus López, Encarnación (Historia y Política, 2019)
The history of the Saharian conflict still contains some aspects to be studied, despite the number of essays that have been published in recent years on the subject. Among them, some actors who have gone almost unnoticed, at least for the Spanish historiography. Mauritania is one of them. This paper analyzes the role of that seemingly weak young country in the Sahara crisis making use of US and French diplomatic sources. Its motivations, the evolution of its positions and the political shift from the extreme defense of the principle of self-determination for the Sahara, along with Algeria, to its participation with Morocco in an adventure whose result will be key in the drift of the young Republic towards the abyss. All this process under the examination and/or action of two powers present in the conflict, to a greater or lesser extent: the US and France.